Antifungal and anti-biofilm effects of shallot (Allium ascalonicum) aqueous extract on Candida albicans - Tzu Shan Ng; Ley Juen Looi; Ban Shui Ong; Pei Pei Chong (Shahrekord University of Medical Sciences, 2018)
Introduction: The limited option to combat fungal threat has raised the interest in seeking alternative anti-fungal compounds. This study aimed to determine the antifungal property of aqueous-extracted shallot (Allium ascalonicum) against Candida albicans, a medically important yeast pathogen. The anti-biofilm property of A. ascalonicum aqueous extract was also investigated. Methods: The antifungal effect of A. ascalonicum aqueous extract on C. albicans was screened using disc diffusion assay and the minimum inhibitory concentration (MIC) was determined using broth macrodilution. Subsequently, the anti-biofilm property of A. ascalonicum aqueous extract was investigated using 2,3-bis(2-methoxy-4-nitro-5-sulfophenyl)-5-[(phenylamino) carbonyl]-2 H-tetrazolium hydroxide (XTT) reduction assay, crystal violet (CV) assay, and microscopic examination. Results: A zone of C. albicans growth inhibition was observed at 10 and 20 g/mL of A. ascalonicum aqueous extract. The MIC of A. ascalonicum aqueous extract was found at 10 g/mL. Significant differences were found between A. ascalonicum aqueous extract -treated and non-treated C. albicans in term of biofilm formation activity (XTT assay) and the quantity of biofilm formed (CV assay). Conclusion: Using a simple and inexpensive extraction procedure, this study revealed the antifungal property of A. ascalonicum aqueous extract, which could be useful in exploring novel antifungal compound.